2017
DOI: 10.1659/mrd-journal-d-15-00041.1
|View full text |Cite
|
Sign up to set email alerts
|

Gendered Responses to Drought in Yunnan Province, China

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Research focusing on migration in dryland areas of Asia and in South America offers similar conclusions with respect to the gendered impacts, multidirectionality of responses, confounding impacts of deforestation and land degradation and the diversity of migration outcomes in response to droughts (Alam, 2015; Castro, 2019; Gray & Mueller, 2012b; Jülich, 2011; Kabir et al, 2018; Pires Ramos & Yamamoto, 2018; Su et al, 2017; Ye et al, 2011). In most regions, the bulk of studies focuses on drought effects on migration patterns within countries, but there is a notable cluster of studies on international drought‐related migration between Mexico and the United States.…”
Section: Existing Literature On Rural Migration Responses To Droughtmentioning
confidence: 89%
“…Research focusing on migration in dryland areas of Asia and in South America offers similar conclusions with respect to the gendered impacts, multidirectionality of responses, confounding impacts of deforestation and land degradation and the diversity of migration outcomes in response to droughts (Alam, 2015; Castro, 2019; Gray & Mueller, 2012b; Jülich, 2011; Kabir et al, 2018; Pires Ramos & Yamamoto, 2018; Su et al, 2017; Ye et al, 2011). In most regions, the bulk of studies focuses on drought effects on migration patterns within countries, but there is a notable cluster of studies on international drought‐related migration between Mexico and the United States.…”
Section: Existing Literature On Rural Migration Responses To Droughtmentioning
confidence: 89%
“…With yet a prevalent interest on agricultural practices, other resilience and adaptation studies have advanced understanding over the major social factors that enhance resilience and adaptation potentials (Carrico et al, 2019 ; Chen et al, 2014 ; Downard & Endter‐Wada, 2013 ; Echeverría, 2020 ; Kruse & Seidl, 2013 ; Laforge & McLeman, 2013 ; Li et al, 2012 ; Moore et al, 2018 ; Pendley et al, 2020 ; Ranjan, 2014 ; Sapountzaki & Daskalakis, 2018 ; Su et al, 2017 ; Wenger et al, 2017 ; Wiener et al, 2016 ; Wreford & Adger, 2010 ; Yila & Resurreccion, 2014 ). Socioeconomic status, previous experiences of drought, access to social capital, and gender are the most investigated aspects both at individual and household level.…”
Section: From Impacts To Recovery? Social Resilience and Adaptation T...mentioning
confidence: 99%
“…Most of the literature uses quantitative surveys, statistical analyses, and mathematical models to measure resilience levels and estimate the correlation between prevailing adaptation strategies and socioenvironmental characteristics of the area (Carrico et al, 2019 ; Chen et al, 2014 ; Du et al, 2018 ; Gonzales & Ajami, 2017 ; Hund et al, 2018 ; Lindsay et al, 2017 ; Moore et al, 2018 ; Pendley et al, 2020 ; Quiroga et al, 2011 ; Sapountzaki & Daskalakis, 2018 ; Su et al, 2017 ; van Duinen et al, 2016 ; Yates et al, 2013 ; Yila & Resurreccion, 2014 ). Sociohydrological studies apply numerical models to simulate adaptive behaviors of different stakeholders and their long‐term socioenvironmental dynamics (Hund et al, 2018 ; van Duinen et al, 2016 ; Wens et al, 2019 ).…”
Section: From Impacts To Recovery? Social Resilience and Adaptation T...mentioning
confidence: 99%
“…FTA research (Su et al 2017) showed that although women were traditionally excluded from being village "water managers" (responsible for water tank and pipe maintenance and domestic water allocation at the village level) and considered incapable in this area, they became increasingly active in A worker shells Brazil nuts, Puerto Maldonado, Madre de Dios, Peru.…”
Section: Climate Actionmentioning
confidence: 99%